Human resource management : Gaining a competitive advantage - Noe, Raymond A.; Hollenbeck, John R.; Gerhart, Bary; Wright, Patrick M. (New York McGraw Hill, 2019)
Human Resource Management: Gaining a Competitive Advantage was developed to teach students how to strategically overcome challenges within organizations and gain a competitive advantage for their companies.
Keywords: Quản trị kinh doanh